Étude des effets thérapeutiques et toxiques de l'Aloe Vera Miller récoltée dans la région de Mostaganem - MelleBoudinar, Fatiha; Allouti, Lyna (My University, 2020)
Aloe Vera or Aloe barbadensis Miller is a green plant in the Liliaceae family with fleshy leaves reminiscent of a cactus, native to South Africa. For more than 5000 years, Aloe Vera is used for its healing and hydrating virtues which would be mainly due to a polysaccharide : acemannan, although other compounds also come into play. These properties have been confirmed by numerous studies. discussed in this note. Nowadays Aloe Vera is present in many products that can be found in pharmacies to treat small everyday ailments. However, we must remain vigilant about the composition of these products which could prove ineffective due to uncontrolled harvest and manufacture. The method of cold stabilization is essential for the manufacture of the gel and that is why the pure titrated products will be more ecommended in order to fully benefit from the virtues of this plant.
Keywords: Aloe Vera; inflammation of Aloe vera; toxicity